Preliminary Clinical Experience with Cholecystokinin-2 Receptor PET/CT Using the68Ga-Labeled Minigastrin Analog DOTA-MGS5 in Patients with Medullary Thyroid Cancer - Elisabeth von Guggenberg; Christian Uprimny; Maximilian Klinger; Boris Warwitz; Anna Sviridenko; Steffen Bayerschmidt; Gianpaolo di Santo; Irene Virgolini (2023)
PET/CT with the new 68Ga-labeled minigastrin analog DOTA-dGlu-Ala-Tyr-Gly-Trp-(N-Me)Nle-Asp-1-Nal-NH2 (68Ga-DOTA-MGS5) was performed on patients with advanced medullary thyroid cancer (MTC) to evaluate cholecystokinin-2 receptor expression status. Methods: Six patients with advanced MTC underwent PET/CT with 68Ga-DOTA-MGS5. From the images acquired 1 and 2 h after injection, preliminary data on the biodistribution and tumor-targeting properties were evaluated in a retrospective analysis. Results: In total, 87 lesions with increased radiotracer uptake considered malignant were detected (2 local recurrences, 8 lymph node lesions, 27 liver lesions, and 50 bone lesions). In general, radiotracer accumulation in lesions was higher at 2 h than at 1 h after injection (mean SUVmax, 7.2 vs. 6.0, respectively; mean SUVmean, 4.4 vs. 3.6, respectively). Conclusion: The preliminary results clearly demonstrate the potential of 68Ga-DOTA-MGS5 PET/CT in detecting local recurrence and metastases in patients with advanced MTC.